GPS and compass technologies as tools for land demarcation and conservation in the Peruvian Amazon - Fuhrmann, Angie, author; Rehms, Jessica, narrator; Fuhrmann, Angie, producer (Colorado State University. Libraries, 2011)
This is the audio of a video presentation which is a summation of Angie Fuhrmann's graduate field work at Colorado State University and fellowship through the Center for Collaborative Conservation in conjunction with Village Earth and the Shipibo community, Santa Rosa de Dinamarca. It outlines the threats to the cultural and biodiversity in the central Peruvian Amazon and then talks about a collaboration to conserve them through local empowerment.
Date taken from website.
Video presentation: https://www.youtube.com/watch?v=c0Zo8MFXIkY
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Peruvian Amazon -- Development -- Conflict of interests; Peruvian Amazon -- Development -- Conflict management; Conservation -- Peruvian Amazon; Collaboration -- Peruvian Amazon; Shipibo community